Polarizing plate with phase difference layer and image display device
By optimizing structural parameters such as the total thickness, the absorption axis angle of the polarizer and the elastic modulus of the protective layer in the prior art, the shortcomings of the polarizer in the thinning and bending properties are solved, and excellent visual recognition and bending properties are achieved.
Patent Information
- Application Number
- CN202180069199.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-10-26
- Filing Date
- 2021-05-31
- Publication Date
- 2025-03-25
- Estimated Expiration
- 2041-05-31
AI Technical Summary
The existing polarizer with phase difference layer has shortcomings in terms of thinning and bending properties, and it is difficult to meet the diverse requirements of visual recognition and bending properties of image display devices.
A polarizer with a phase difference layer is designed, which includes a polarizer, a polarizer and a protective layer, and a phase difference layer is provided on the visual side of the polarizer. The total thickness of the polarizer is controlled below 80 μm, the angle between the absorption shaft and the bending shaft of the polarizer is adjusted to 30° to 60°, and the elastic modulus of the protective layer is optimized to be below 5000MPa.
A polarizer with a phase difference layer with excellent visual recognition and excellent bending properties of polarized sunglasses is realized, and the thinning and diversified requirements of the image display device are met.
Smart Images

Figure CN116324604B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a polarizing plate with a phase difference layer and an image display device. Background Art
[0002] In recent years, image display devices represented by liquid crystal display devices and electroluminescent (EL) display devices (for example, organic EL display devices, inorganic EL display devices) have rapidly become popular. Polarizers and phase difference plates are representatively used in image display devices. In practice, polarizers with phase difference layers that integrate polarizers and phase difference plates are widely used (for example, Japanese Patent Document 1), but recently, as the demand for thinning of image display devices has become stronger, the demand for thinning of polarizers with phase difference layers has also become stronger. Furthermore, as the use of image display devices expands, the requirements for image display devices have become diversified. For example, with respect to smart phones, it is required to be foldable, and to improve visibility through polarized sunglasses. Therefore, it is strongly desired to have a polarizer with a phase difference layer that can realize the above-mentioned image display device.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent No. 3325560 Summary of the invention
[0006] Problems to be solved by the invention
[0007] The present invention has been made to solve the above-mentioned conventional problems, and its main object is to provide a polarizing plate with a retardation layer which has a simple structure, excellent visibility through polarized sunglasses, and excellent bendability.
[0008] Means for solving problems
[0009] The polarizing plate with a phase difference layer of the present invention is used for a bendable image display device. The polarizing plate with a phase difference layer comprises: a polarizing plate, which includes a polarizer and a protective layer located on at least one side of the polarizer; and a phase difference layer, which is arranged on the side of the polarizer opposite to the visual recognition side and has a circular polarization function or an elliptically polarized light function, the total thickness of the polarizing plate with a phase difference layer is less than 80 μm, the angle between the bending axis of the image display device and the absorption axis of the polarizer is 30° to 60°, and the elastic modulus of the protective layer is less than 5000 MPa.
[0010] In one embodiment, the total thickness of the polarizing plate with a retardation layer is 60 μm or less.
[0011] In one embodiment, the polarizer has a thickness of 10 μm or less.
[0012] In one embodiment, the polarizing plate includes a protective layer only on the side of the polarizer opposite to the retardation layer.
[0013] In one embodiment, the elastic modulus of the protective layer is 4000 MPa or less.
[0014] In one embodiment, the protective layer has a thickness of 45 μm or less.
[0015] In one embodiment, the angle formed between the bending axis and the absorption axis of the polarizer is 40° to 50°.
[0016] In one embodiment, the phase difference layer is an alignment solidified layer of a liquid crystal compound.
[0017] In one embodiment, the phase difference layer is a single layer, the Re(550) of the phase difference layer is 100nm to 190nm, the Re(450) / Re(550) of the phase difference layer is greater than 0.8 and less than 1, and the angle between the slow axis of the phase difference layer and the absorption axis of the polarizer is 40° to 50°. In one embodiment, the polarizer with a phase difference layer further has another phase difference layer outside the phase difference layer, and the refractive index characteristics of the other phase difference layer show the relationship of nz>nx=ny.
[0018] In one embodiment, the phase difference layer has a stacked structure of an orientation solidified layer of a first liquid crystal compound and an orientation solidified layer of a second liquid crystal compound; the Re(550) of the orientation solidified layer of the first liquid crystal compound is 200nm~300nm, and the angle formed by its slow axis and the absorption axis of the polarizer is 10°~20°; the Re(550) of the orientation solidified layer of the second liquid crystal compound is 100nm~190nm, and the angle formed by its slow axis and the absorption axis of the polarizer is 70°~80°.
[0019] According to another aspect of the present invention, there is provided an image display device comprising the polarizing plate with a retardation layer.
[0020] Effects of the Invention
[0021] According to an embodiment of the present invention, by optimizing the angle between the bending axis and the absorption axis of the polarizer in a polarizing plate with a phase difference layer when applied to a bendable image display device, and optimizing the elastic modulus of the protective layer, a polarizing plate with a phase difference layer can be realized which has a simple structure, excellent visibility through polarized sunglasses, and excellent bendability. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1This is a schematic perspective view showing a curved state of an image display device to which a polarizing plate with a retardation layer according to an embodiment of the present invention is applied.
[0023] Figure 2 This is a schematic plan view of a polarizing plate with a retardation layer according to one embodiment of the present invention.
[0024] Figure 3 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to one embodiment of the present invention.
[0025] Figure 4 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to another embodiment of the present invention. DETAILED DESCRIPTION
[0026] Hereinafter, embodiments of the present invention will be described, but the present invention is not limited to these embodiments.
[0027] (Definition of Terms and Symbols)
[0028] The definitions of terms and symbols in this specification are as follows.
[0029] (1) Refractive index (nx, ny, nz)
[0030] “nx” is the refractive index in the direction of the maximum refractive index in the plane (ie, the slow axis direction), “ny” is the refractive index in the direction orthogonal to the slow axis in the plane (ie, the fast axis direction), and “nz” is the refractive index in the thickness direction.
[0031] (2) In-plane phase difference (Re)
[0032] "Re(λ)" is the in-plane phase difference measured at 23°C using light of wavelength λnm. For example, "Re(550)" is the in-plane phase difference measured at 23°C using light of wavelength 550nm. Re(λ) is calculated using the formula: Re(λ) = (nx-ny) × d when the thickness of the layer (film) is set to d (nm).
[0033] (3) Retardation in the thickness direction (Rth)
[0034] "Rth(λ)" is the phase difference in the thickness direction measured by light of wavelength λnm at 23°C. For example, "Rth(550)" is the phase difference in the thickness direction measured by light of wavelength 550nm at 23°C. Rth(λ) is calculated by the formula: Rth(λ) = (nx-nz) × d when the thickness of the layer (film) is set to d (nm).
[0035] (4) Nz coefficient
[0036] The Nz coefficient is obtained by using Nz=Rth / Re.
[0037] (5) Angle
[0038] In this specification, when an angle is mentioned, the angle includes both clockwise and counterclockwise directions relative to a reference direction. Therefore, for example, "45°" means ±45°; and for example, "30° to 60°" means +30° to +60° or -30° to -60°.
[0039] A. Overall structure of polarizing plate with phase difference layer
[0040] Figure 1 This is a schematic perspective view showing a curved state of an image display device to which a polarizing plate with a phase difference layer according to an embodiment of the present invention is applied; Figure 2 It is a schematic top view of a polarizing plate with a phase difference layer according to one embodiment of the present invention; Figure 3 This is a schematic cross-sectional view of a polarizing plate with a phase difference layer according to one embodiment of the present invention; Figure 4 This is a schematic cross-sectional view of a polarizing plate with a retardation layer according to another embodiment of the present invention. Figure 3 The polarizing plate 100 with a phase difference layer in the example shown typically has a polarizing plate 10 and a phase difference layer 20 in order from the visual side. In the example shown, the polarizing plate 10 includes a polarizer 11 and protective layers 12 and 13 located on both sides of the polarizer 11. Depending on the purpose, one of the protective layers 12 and 13 can also be omitted. In one embodiment, the polarizing plate 10 has a protective layer 12 only on the visual side of the polarizer 11 (the side opposite to the phase difference layer 20). The constituent elements of the polarizing plate with a phase difference layer are typically bonded via any appropriate adhesive layer (adhesive layer or adhesive layer: not shown). In terms of practicality, an adhesive layer (not shown) is provided on the side of the phase difference layer 20 opposite to the polarizing plate 10 (that is, as the outermost layer on the side opposite to the visual side), and the polarizing plate with a phase difference layer can be attached to the image display panel. Furthermore, on the surface of the adhesive layer, it is preferred to temporarily bond a release film (not shown) before the polarizing plate with a phase difference layer is used. By temporarily adhering the release film, the pressure-sensitive adhesive layer can be protected and a roll of a polarizing plate with a retardation layer can be formed.
[0041] like Figure 1 As shown in FIG. 1 , a polarizing plate with a phase difference layer is used in a bendable image display device. Figure 1 and 2As shown, in the polarizer with a phase difference layer, the angle between the bending axis F of the image display device and the absorption axis A of the polarizer 11 is 30° to 60°, preferably 35° to 55°, more preferably 40° to 50°, further preferably 42° to 48°, and particularly preferably about 45°. If it is the above-mentioned structure, there is no need to form a specific layer on the viewing side of the polarizer with a phase difference layer (representatively, a layer that imparts (elliptical) circular polarization function such as a λ / 4 plate, an ultra-high phase difference layer such as an in-plane phase difference Re (550) exceeding 1000nm), so that excellent visibility can be achieved when viewing through polarized sunglasses. Therefore, the polarizer with a phase difference layer of an embodiment of the present invention has a small number of layers, so it is simple and low in cost, resulting in a thin shape. Furthermore, if it is the above-mentioned structure, excellent bendability (bendability) can be achieved through the synergistic effect of optimizing the elastic modulus of the protective layer. In more detail, when the bending axis is parallel to the absorption axis of the polarizer, the polarizer with a phase difference layer (substantially a polarizer) becomes very easy to break. On the other hand, it becomes difficult to break when the bending axis is orthogonal to the absorption axis of the polarizer, but the visibility when viewed through polarized sunglasses is extremely insufficient. By optimizing in such a way that the bending axis forms the above-mentioned specified angle with the absorption axis of the polarizer, it is possible to balance the excellent bending (bending) and the excellent visibility when viewed through polarized sunglasses. Furthermore, in the example shown in the figure, the bending axis F is the short side direction of the image display device, but the bending axis F may also be the long side direction, or may be a direction (oblique direction) having a specified angle relative to the long side direction or the short side direction. By specifying the absorption axis direction relative to the bending axis direction, the above-mentioned effect can be obtained even when the polarizer with a phase difference layer is applied to an image display device of a shape other than a rectangle (for example, a circle, an ellipse, a triangle, or an amorphous shape).
[0042] The total thickness of the polarizer with a phase difference layer (the total thickness of the polarizer, the phase difference layer, and the adhesive layer stacked thereon) is 80 μm or less, preferably 70 μm or less, more preferably 60 μm or less, further preferably 50 μm or less, and particularly preferably 40 μm or less. The total thickness of the polarizer with a phase difference layer may be, for example, 25 μm or more. According to an embodiment of the present invention, even with the very small total thickness described above, excellent visibility when viewed through polarized sunglasses can be achieved. In other words, the polarizer with a phase difference layer can make the total thickness very small even when used for purposes such as viewing through polarized sunglasses. As a result, the second moment of section during bending becomes smaller, and the stress applied to each constituent element (layer) becomes smaller. Therefore, not only can excellent visibility when viewed through sunglasses be achieved, but also excellent bendability (bending) can be achieved.
[0043] In an embodiment of the present invention, the elastic modulus of the protective layer 12 and / or 13 is less than 5000MPa, preferably less than 4500MPa, more preferably less than 4000MPa, and further preferably less than 3500MPa. The lower limit of the elastic modulus of the protective layer may be, for example, 2000MPa. Preferably, the polarizer with a phase difference layer (substantially a polarizer) has only a protective layer 12, and the elastic modulus of the protective layer 12 is the above range. In the case where the elastic modulus of the protective layer is too large, the compressive stress applied to the protective layer becomes larger when the strain during bending is the same. As a result, in the case of repeated bending, the protective layer becomes prone to cracking (cracking). By optimizing the elastic modulus of the protective layer to the above range, cracking during bending can be suppressed, and excellent bending (bending) can be achieved. Furthermore, the elastic modulus can be measured according to JIS Z 2284.
[0044] The phase difference layer 20 has a circular polarization function or an elliptically polarized light function. The phase difference layer 20 is typically an oriented solidified layer of a liquid crystal compound (liquid crystal oriented solidified layer). By using a liquid crystal compound, the difference between nx and ny of the obtained phase difference layer can be significantly larger than that of a non-liquid crystal material, so the thickness of the phase difference layer used to obtain the desired in-plane phase difference can be significantly reduced. Therefore, a significant thinning of the polarizer with a phase difference layer can be achieved. As a result, excellent bendability (bendability) as described above can be achieved. In this specification, an "oriented solidified layer" refers to a layer in which a liquid crystal compound is oriented in a prescribed direction within the layer and its orientation state is fixed. Furthermore, an "oriented solidified layer" refers to a concept of an oriented solidified layer obtained by curing a liquid crystal monomer as described below. In the phase difference layer 20, a rod-shaped liquid crystal compound is typically oriented (parallel oriented) in a state of being arranged along the slow axis direction of the phase difference layer. The phase difference layer 20 can be as Figure 3 As shown in the single layer, it can also be Figure 4 As shown, it has a stacked structure of two or more layers.
[0045] The polarizer with phase difference layer may further include other optical functional layers. The type, characteristics, quantity, combination, configuration position, etc. of the optical functional layer that can be set in the polarizer with phase difference layer can be appropriately set according to the purpose. For example, the polarizer with phase difference layer may further have a conductive layer or an isotropic substrate with a conductive layer (neither of which is shown in the figure). The conductive layer or the isotropic substrate with a conductive layer is typically arranged on the outside of the second phase difference layer 22 (the side opposite to the polarizer 10). The conductive layer or the isotropic substrate with a conductive layer is typically an arbitrary layer set as needed, and may also be omitted. Furthermore, in the case of setting a conductive layer or an isotropic substrate with a conductive layer, the polarizer with phase difference layer can be applied to a so-called internal touch panel type input display device in which a touch sensor is assembled between an image display unit (e.g., an organic EL unit) and a polarizer. In addition, for example, the polarizer with phase difference layer may further include other phase difference layers. The optical properties (for example, refractive index properties, in-plane phase difference, Nz coefficient, photoelastic modulus), thickness, arrangement position, etc. of the other phase difference layers can be appropriately set according to the purpose.
[0046] Hereinafter, the components of the polarizing plate with a retardation layer will be described in more detail.
[0047] B. Polarizer
[0048] B-1. Polarizer
[0049] Any appropriate polarizer can be adopted as the polarizer 11. For example, the resin film forming the polarizer may be a single-layer resin film or a laminate of two or more layers.
[0050] Specific examples of polarizers composed of a single-layer resin film include: hydrophilic polymer films such as polyvinyl alcohol (PVA) films, partially formalized PVA films, and partially saponified films of ethylene-vinyl acetate copolymers, which are dyed and stretched using dichroic substances such as iodine or dichroic dyes; polyene-based oriented films such as dehydrated PVA films or dehydrochlorinated polyvinyl chloride films, etc. In terms of excellent optical properties, it is preferred to use a polarizer obtained by dyeing a PVA film with iodine and uniaxially stretching it.
[0051] The dyeing using iodine can be performed, for example, by immersing the PVA membrane in an iodine aqueous solution. The stretching ratio of the uniaxial stretching is preferably 3 to 7 times. The stretching can be performed after the dyeing treatment or simultaneously with the dyeing. In addition, the dyeing can also be performed after the stretching. As required, the PVA membrane is subjected to swelling treatment, cross-linking treatment, cleaning treatment, drying treatment, etc. For example, by immersing the PVA membrane in water for washing before dyeing, not only can the stains or anti-adhesive agent on the surface of the PVA membrane be washed, but also the PVA membrane can be swollen to prevent uneven dyeing.
[0052] As a specific example of a polarizer obtained using a laminate, there can be cited a laminate of a resin substrate and a PVA-based resin layer (PVA-based resin film) laminated on the resin substrate, or a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate. The polarizer obtained using a laminate of a resin substrate and a PVA-based resin layer formed by coating on the resin substrate can be made, for example, by the following steps: applying a PVA-based resin solution to a resin substrate, drying it to form a PVA-based resin layer on the resin substrate, thereby obtaining a laminate of the resin substrate and the PVA-based resin layer; and stretching and dyeing the laminate to make the PVA-based resin layer into a polarizer. In this embodiment, it is preferred that a polyvinyl alcohol-based resin layer containing a halide and a polyvinyl alcohol-based resin is formed on one side of the resin substrate. As for stretching, it typically includes immersing the laminate in an aqueous boric acid solution for stretching. Furthermore, stretching may further include the following steps as needed: before stretching in a boric acid aqueous solution, the laminate is stretched in the air at a high temperature (for example, above 95°C). Moreover, in the present embodiment, it is preferred that the laminate is subjected to the following drying and shrinking treatment, that is, by conveying along the length direction on one side and heating on the other side, so that the width direction shrinks by more than 2%. Representatively speaking, the manufacturing method of the present embodiment includes sequentially performing an auxiliary stretching treatment in the air, a dyeing treatment, an underwater stretching treatment, and a drying and shrinking treatment on the laminate. By introducing auxiliary stretching, the crystallinity of PVA can also be improved in the case of coating PVA on a thermoplastic resin, and high optical properties can be achieved. In addition, by simultaneously improving the orientation of PVA in advance, when immersed in water in a subsequent dyeing process or a stretching process, problems such as a decrease in orientation or dissolution of PVA can be prevented, and high optical properties can be achieved. Furthermore, when the PVA-based resin layer is immersed in a liquid, the orientation disorder and the decrease in orientation of the polyvinyl alcohol molecules can be suppressed compared to the case where the PVA-based resin layer does not contain a halide. Thus, the optical properties of the polarizer obtained by the treatment process of immersing the laminate in a liquid through dyeing treatment and underwater stretching treatment can be improved. Furthermore, the optical properties can be improved by shrinking the laminate in the width direction by utilizing a drying shrinkage treatment. The obtained laminate of the resin substrate / polarizer can be used directly (that is, the resin substrate can be used as a protective layer of the polarizer), or the resin substrate can be peeled off from the laminate of the resin substrate / polarizer, and any appropriate protective layer can be stacked on the peeling surface according to the purpose. The details of the manufacturing method of the above-mentioned polarizer are recorded in, for example, Japanese Patent Publication No. 2012-73580 and Japanese Patent No. 6470455. All the records in the above-mentioned gazette are cited in this specification in the form of reference.
[0053] The thickness of the polarizer is preferably 15 μm or less, more preferably 12 μm or less, further preferably 10 μm or less, particularly preferably 3 μm to 10 μm, and particularly preferably 3 μm to 8 μm. If the thickness of the polarizer is within the above range, the desired total thickness can be achieved, and excellent bendability can be achieved.
[0054] The polarizer preferably exhibits absorption dichroism at any wavelength of 380 nm to 780 nm. The single transmittance of the polarizer is preferably 41.5% to 46.0%, more preferably 43.0% to 46.0%, and further preferably 44.5% to 46.0%. The polarization degree of the polarizer is preferably 97.0% or more, more preferably 99.0% or more, and further preferably 99.9% or more.
[0055] B-2. Protective layer
[0056] As long as the above elastic modulus can be obtained respectively, the protective layers 12 and 13 can be formed of any appropriate film that can be used as a protective layer of a polarizer. Specific examples of the material that becomes the main component of the film include: cellulose resins such as triacetyl cellulose (TAC), or polyesters, polyvinyl alcohols, polycarbonates, polyamides, polyimides, polyether sulfones, polysulfones, polystyrenes, cyclic olefins (e.g., polynorbornene), polyolefins, (meth) acrylic acid, acetates and other transparent resins.
[0057] The polarizing plate with a retardation layer is typically disposed on the viewing side of the image display device, and the protective layer 12 is disposed on the viewing side. Therefore, the protective layer 12 may be subjected to surface treatment such as hard coating, anti-reflection treatment, anti-blocking treatment, anti-glare treatment, etc. as needed.
[0058] The thickness of each of the protective layers 12 and 13 is preferably 60 μm or less, more preferably 45 μm or less, and further preferably 10 μm to 40 μm. When surface treatment is applied, the thickness of the protective layer 12 includes the thickness of the surface treatment layer.
[0059] C. Phase difference layer
[0060] As described above, the phase difference layer 20 may be a single layer or may have a stacked structure of two or more layers.
[0061] When the phase difference layer 20 is a single layer, the phase difference layer can representatively function as a λ / 4 plate. Specifically, the Re (550) of the phase difference layer is preferably 100nm to 180nm, more preferably 110nm to 170nm, and further preferably 110nm to 160nm. The thickness of the phase difference layer can be adjusted in a manner that can obtain the desired in-plane phase difference of the λ / 4 plate. The thickness of the phase difference layer can be, for example, 1.0μm to 2.5μm. In the present embodiment, the angle between the slow axis of the phase difference layer and the absorption axis of the polarizer is preferably 40° to 50°, more preferably 42° to 48°, and further preferably 44° to 46°. In this embodiment, the polarizing plate with a phase difference layer may also further have a phase difference layer (not shown) showing a refractive index characteristic of nz>nx=ny on the outside of the phase difference layer 20. When the phase difference layer is a single layer, the phase difference layer preferably shows an inverse wavelength dispersion characteristic in which the phase difference value increases according to the wavelength of the measured light. In this case, Re(450) / Re(550) of the retardation layer is preferably 0.8 or more and less than 1, and more preferably 0.8 to 0.95.
[0062] When the phase difference layer 20 has a stacked structure, the phase difference layer is typically as follows: Figure 4It has a two-layer structure with an H layer 21 and a Q layer 22 in this order from the side of the polarizer. The H layer can typically function as a λ / 2 plate, and the Q layer can typically function as a λ / 4 plate. Specifically, Re(550) of the H layer is preferably 200 nm to 300 nm, more preferably 220 nm to 290 nm, and further preferably 230 nm to 280 nm; Re(550) of the Q layer is preferably 100 nm to 180 nm, more preferably 110 nm to 170 nm, and further preferably 110 nm to 150 nm. The thickness of the H layer can be adjusted in such a way as to obtain the desired in-plane retardation of the λ / 2 plate. When the H layer is a liquid crystal alignment cured layer, its thickness can be, for example, 2.0 μm to 4.0 μm. The thickness of the Q layer can be adjusted in such a way as to obtain the desired in-plane retardation of the λ / 4 plate. When the Q layer is a liquid crystal alignment cured layer, its thickness can be, for example, 1.0 μm to 2.5 μm. In this embodiment, the angle formed by the slow axis of the H layer and the absorption axis of the polarizer is preferably 10° to 20°, more preferably 12° to 18°, and further preferably 12° to 16°; the angle formed by the slow axis of the Q layer and the absorption axis of the polarizer is preferably 70° to 80°, more preferably 72° to 78°, and further preferably 72° to 76°. Furthermore, the arrangement order of the H layer and the Q layer can be reversed, and the angle formed by the slow axis of the H layer and the absorption axis of the polarizer and the angle formed by the slow axis of the Q layer and the absorption axis of the polarizer can also be reversed. When the retardation layer has a laminated structure, each layer (for example, the H layer and the Q layer) can exhibit an inverse wavelength dispersion characteristic in which the retardation value increases according to the wavelength of the measurement light, a positive wavelength dispersion characteristic in which the retardation value decreases according to the wavelength of the measurement light, or a flat wavelength dispersion characteristic in which the retardation value remains substantially unchanged regardless of the wavelength of the measurement light.
[0063] Typically, the refractive index characteristics of the retardation layer (each layer in the case of having a laminated structure) show a relationship of nx > ny = nz. Furthermore, "ny = nz" includes not only the case where ny and nz are exactly equal but also the case where they are substantially equal. Therefore, within the range that does not impair the effects of the present invention, there may be cases where ny > nz or ny < nz. The Nz coefficient of the retardation layer is preferably 0.9 to 1.5, more preferably 0.9 to 1.3.
[0064] Typically, the retardation layer is a liquid crystal alignment cured layer as described above. As the liquid crystal compound, for example, a liquid crystal compound having a nematic phase (nematic liquid crystal) can be cited. As the above liquid crystal compound, for example, a liquid crystal polymer or a liquid crystal monomer can be used. The mechanism of manifestation of the liquid crystallinity of the liquid crystal compound can be lyotropic or thermotropic. The liquid crystal polymer and the liquid crystal monomer can be used alone or in combination.
[0065] In the case where the liquid crystal compound is a liquid crystal monomer, the liquid crystal monomer is preferably a polymerizable monomer and a cross-linkable monomer. The reason is that by polymerizing or cross-linking (i.e., curing) the liquid crystal monomer, the orientation state of the liquid crystal monomer can be fixed. After the liquid crystal monomer is oriented, for example, as long as the liquid crystal monomers are polymerized or cross-linked with each other, the above-mentioned orientation state can be fixed. Here, polymers are formed by polymerization, and three-dimensional network structures are formed by cross-linking, but they are non-liquid crystal. Therefore, the phase difference layer formed, for example, will not undergo the transformation to the liquid crystal phase, the glass phase, and the crystalline phase that is affected by temperature changes, which is unique to liquid crystal compounds. As a result, the phase difference layer becomes a phase difference layer that is not affected by temperature changes and has extremely excellent stability.
[0066] The temperature range in which the liquid crystal monomer exhibits liquid crystallinity varies depending on the type of the liquid crystal monomer. Specifically, the temperature range is preferably 40°C to 120°C, more preferably 50°C to 100°C, and most preferably 60°C to 90°C.
[0067] As the above-mentioned liquid crystal monomer, any appropriate liquid crystal monomer can be used. For example, the polymerizable mesogen compounds described in Japanese Patent Table 2002-533742 (WO00 / 37585), EP358208 (US5211877), EP66137 (US4388453), WO93 / 22397, EP0261712, DE19504224, DE4408171 and GB2280445 can be used. As a specific example of the above-mentioned polymerizable mesogen compound, for example, the trade name LC242 of BASF, the trade name E7 of Merck, and the trade name LC-Sillicon-CC3767 of Wacker-Chem can be listed. As the liquid crystal monomer, for example, a nematic liquid crystal monomer is preferably used.
[0068] D. Image display device
[0069] The polarizer with a phase difference layer described in items A to C above can be applied to an image display device. Therefore, an image display device including a polarizer with a phase difference layer is also included in an embodiment of the present invention. The image display device typically includes an image display unit, and a polarizer with a phase difference layer attached to the image display unit via an adhesive layer. As representative examples of image display devices, there can be listed: a liquid crystal display device, an electroluminescent (EL) display device (such as an organic EL display device, an inorganic EL display device). The image display device can be bent as described above, and preferably can be folded. In the above-mentioned image display device, the effect of the polarizer with a phase difference layer of an embodiment of the present invention becomes significant.
[0070] [Example]
[0071] The present invention will be described in detail below using examples, but the present invention is not limited to these examples. The measuring methods of each characteristic are as follows. In addition, unless otherwise specified, the "parts" and "%" in the examples and comparative examples are based on weight.
[0072] (1) Thickness
[0073] The thickness of 10 μm or less was measured using an interference film thickness meter (product name "MCPD-3000" manufactured by Otsuka Electronics Co., Ltd.) and the thickness exceeding 10 μm was measured using a digital micrometer (product name "KC-351C" manufactured by ANRIC Co., Ltd.).
[0074] (2) Elastic modulus
[0075] The measurement is carried out in accordance with JIS Z 2284. Specifically, it is as follows. A short strip sample piece with a width of 10 mm and a length of 100 mm is cut out from the protective layer used in the embodiments and comparative examples, and a corresponding high-speed continuous automatic stereogrammer (manufactured by Shimadzu Corporation) is used to stretch the sample piece in the length direction under the following conditions, and the elastic modulus is calculated based on the obtained SS (Stress-Strain) curve. As the measurement conditions, the stretching speed is 50 mm / min, the distance between the chucks is 100 mm, and the measurement temperature is room temperature (25°C). The method for calculating the elastic modulus based on the SS curve is as follows. Draw a tangent at the initial rise of the SS curve, read the strength at the position where the extension of the tangent becomes 100% elongation, divide it by the cross-sectional area of the sample piece (thickness × sample width (10 mm)) where the value is measured, and use the obtained value as the elastic modulus.
[0076] (3) Bending test
[0077] The polarizer with a phase difference layer obtained in the examples and comparative examples is cut into a size of 100 mm × 55 mm as a measurement sample. Here, the cutting is performed in such a way that the bending axis becomes the short side direction of the measurement sample. A continuous bending test is performed on the measurement sample using a bending tester (product name "CL09 Type D01" manufactured by YUASA SYSTEM Machine Co., Ltd.). The bending is performed at room temperature in such a way that the protective layer on the visual side becomes the inner side. The radius of curvature of the bending is 3 mm. Visually observe whether there is cracking when bending 500,000 times, and evaluate according to the following criteria.
[0078] ○: No cracks were observed
[0079] ×: Cracks confirmed
[0080] (4) Visibility when viewing through polarized sunglasses
[0081] The polarizing plate on the viewing side of a commercially available liquid crystal display device is removed, and the surface after the polarizing plate is removed is cleaned, and the polarizing plate with a phase difference layer obtained in the examples and comparative examples is bonded to the cleaned surface. The absorption axis of the polarizer of the polarizing plate with a phase difference layer is bonded in such a way that the angle with the short side of the liquid crystal display device is 0°, 30°, 40°, 45°, 50°, 60°, and 90°. The liquid crystal display device obtained as described above is made to display the specified text, and the display screen is observed by wearing polarized sunglasses. Here, the absorption axis direction of the polarized sunglasses is aligned with the short side direction and the long side direction of the image display device, and the evaluation is performed according to the following criteria.
[0082] ○: When the absorption axis of the polarized sunglasses is aligned with either the short side or the long side, the content of the displayed screen can be recognized to an understandable degree
[0083] ×: When the absorption axis direction of the polarized sunglasses is aligned with at least one of the short side direction or the long side direction, the content of the display screen cannot be recognized
[0084] [Example 1-1]
[0085] 1. Preparation of polarizer
[0086] As the thermoplastic resin substrate, a long amorphous isophthalic acid copolymer polyethylene terephthalate film (thickness: 100 μm) having a Tg of about 75° C. was used, and one surface of the resin substrate was subjected to a corona treatment.
[0087] To 100 parts by weight of a PVA-based resin prepared by mixing polyvinyl alcohol (degree of polymerization 4200, degree of saponification 99.2 mol%) and acetyl-modified PVA (product name "GOHSEFIMER" manufactured by Nippon Synthetic Chemical Industry Co., Ltd.) in a ratio of 9:1, 13 parts by weight of potassium iodide were added, and the resultant was dissolved in water to prepare a PVA aqueous solution (coating solution).
[0088] The PVA aqueous solution was applied to the corona-treated surface of the resin substrate and dried at 60° C. to form a 13 μm-thick PVA-based resin layer to produce a laminate.
[0089] The obtained laminate was uniaxially stretched to 2.4 times in the longitudinal direction (length direction) in an oven at 130° C. (auxiliary stretching treatment in air).
[0090] Next, the laminate was immersed in an insolubilization bath (boric acid aqueous solution obtained by mixing 4 parts by weight of boric acid with 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (insolubilization treatment).
[0091] Next, the film was immersed in a dyeing bath (an iodine aqueous solution obtained by mixing iodine and potassium iodide in a weight ratio of 1:7 relative to 100 parts by weight of water) at a liquid temperature of 30° C. for 60 seconds while adjusting the concentration so that the monomer transmittance (Ts) of the finally obtained polarizer becomes a specified value (dyeing treatment).
[0092] Next, the film was immersed in a crosslinking bath (boric acid aqueous solution prepared by mixing 3 parts by weight of potassium iodide and 5 parts by weight of boric acid with respect to 100 parts by weight of water) at a liquid temperature of 40° C. for 30 seconds (crosslinking treatment).
[0093] Thereafter, the laminate was immersed in an aqueous boric acid solution (boric acid concentration 4 wt %, potassium iodide concentration 5 wt %) at a liquid temperature of 70°C, and simultaneously uniaxially stretched (underwater stretching treatment) in the longitudinal direction (length direction) between rollers having different peripheral speeds in such a manner that the longitudinal stretching ratio became 5.5 times.
[0094] Thereafter, the laminate was immersed in a cleaning bath (an aqueous solution prepared by mixing 4 parts by weight of potassium iodide with respect to 100 parts by weight of water) at a liquid temperature of 20° C. (cleaning treatment).
[0095] Thereafter, the sheet was brought into contact with a heating roll made of SUS (Steel Special Use Stainless Steel) whose surface temperature was maintained at about 75°C while being dried in an oven maintained at about 90°C (drying shrinkage treatment).
[0096] As described above, a polarizer having a thickness of about 5 μm was formed on the resin substrate to obtain a polarizing plate having a structure of resin substrate / polarizer.
[0097] Furthermore, an HC-TAC film was attached to the surface of the obtained polarizer (the surface on the side opposite to the resin substrate) via an ultraviolet curing adhesive (thickness 1.0 μm) as a protective substrate (protective layer). The HC-TAC film is a film having a hard coating (HC) layer (thickness 7 μm) formed on a triacetylcellulose (TAC) film (thickness 25 μm), and was attached in such a manner that the TAC film became the polarizer side. A polarizing plate having a protective layer / polarizer structure was obtained as described above. The elastic modulus of the protective layer was 3872 MPa.
[0098] 2. Fabrication of phase difference layer
[0099] 10 g of a polymerizable liquid crystal exhibiting a nematic liquid crystal phase (manufactured by BASF: trade name "Paliocolor LC242", represented by the following formula) and 3 g of a photopolymerization initiator for the polymerizable liquid crystal compound (manufactured by BASF: trade name "Irgacure 907") were dissolved in 40 g of toluene to prepare a liquid crystal composition (coating liquid).
[0100] [Chemical formula 1]
[0101]
[0102] The surface of a polyethylene terephthalate (PET) film (38 μm thick) was rubbed with a rubbing cloth to perform an orientation treatment. The orientation treatment direction was set to be 15° relative to the absorption axis of the polarizer when attached to the polarizing plate when viewed from the viewing side. The above-mentioned liquid crystal coating liquid was applied to the orientation treatment surface using a rod coater and heated and dried at 90°C for 2 minutes to orient the liquid crystal compound. The liquid crystal layer formed as described above was irradiated with 1 mJ / cm using a metal halide lamp. 2 The liquid crystal layer is cured by applying light to the PET film, thereby forming a liquid crystal alignment solidification layer A on the PET film. The liquid crystal alignment solidification layer A has a thickness of 2 μm and an in-plane phase difference Re (550) of 270 nm. Furthermore, the liquid crystal alignment solidification layer A has a refractive index distribution of nx>ny=nz. The liquid crystal alignment solidification layer A is used as the W layer.
[0103] The coating thickness was changed, and the orientation treatment direction was made 75° relative to the absorption axis of the polarizer when observed from the visual side. The same operation was performed as above to form a liquid crystal orientation solidified layer B on the PET film. The thickness of the liquid crystal orientation solidified layer B was 1 μm, and the in-plane phase difference Re (550) was 140 nm. Furthermore, the liquid crystal orientation solidified layer B had a refractive index distribution of nx>ny=nz. The liquid crystal orientation solidified layer B was used as the Q layer.
[0104] 3. Preparation of polarizing film with phase difference layer
[0105] The liquid crystal orientation solidification layer A (W layer) and the liquid crystal orientation solidification layer B (Q layer) obtained in the above 2. are sequentially transferred to the polarizer surface of the polarizer obtained in the above 1. At this time, the transfer (lamination) is performed in a manner that the angle formed by the absorption axis of the polarizer and the slow axis of the orientation solidification layer A is 15°, and the angle formed by the absorption axis of the polarizer and the slow axis of the orientation solidification layer B is 75°. Furthermore, each transfer (lamination) is performed via an ultraviolet curing adhesive (thickness 1.0μm). As described above, a polarizer with a phase difference layer having a structure of a protective layer / adhesive / polarizer / adhesive / W layer / adhesive / Q layer is obtained. The thickness of the obtained polarizer with a phase difference layer is 43μm. The polarizer with a phase difference layer is punched into a rectangle of a specific size corresponding to a bendable image display device having a bending axis along the short side direction. Here, the punching is performed in a manner that the absorption axis of the polarizer is 30° relative to the bending axis. The obtained polarizing plate with a retardation layer was subjected to the evaluations of (3) and (4) above. The results are shown in Table 1.
[0106] [Example 1-2] to [Example 1-5] and [Comparative Example 1-1] to [Comparative Example 1-2]
[0107] The polarizing plate with a phase difference layer was obtained in the same manner as in Example 1-1 except that the polarizer was punched out so that the angle between the absorption axis and the bending axis was the angle shown in Table 1. The obtained polarizing plate with a phase difference layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0108] [Example 2-1]
[0109] A polarizing plate having a protective layer / polarizer structure was prepared in the same manner as in Example 1-1. On the other hand, a retardation layer (a single retardation layer showing inverse wavelength dispersion correlation and capable of functioning as a λ / 4 plate) and another retardation layer (positive C plate) were prepared as follows.
[0110] 55 parts of the compound represented by formula (II), 25 parts of the compound represented by formula (III), and 20 parts of the compound represented by formula (IV) were added to 400 parts of cyclopentanone (CPN), and then heated to 60°C and stirred to dissolve. After confirming the dissolution, the mixture was returned to room temperature, and 3 parts of Irgacure 907 (manufactured by BASF Japan Co., Ltd.), 0.2 parts of MEGAFAC F-554 (manufactured by DIC Co., Ltd.), and 0.1 parts of p-methoxyphenol (MEHQ) were added, and further stirred to obtain a solution. The solution was transparent and uniform. The obtained solution was filtered using a 0.20 μm membrane filter to obtain a polymerizable composition. On the other hand, the polyimide solution for the oriented film was applied to a glass substrate with a thickness of 0.7 mm using a spin coating method, dried at 100°C for 10 minutes, and then baked at 200°C for 60 minutes to obtain a coating film. The obtained coating film was rubbed to form an oriented film. The rubbing treatment was performed using a commercially available rubbing device. The polymerizable composition obtained above was applied to the substrate (substantially an oriented film) by spin coating and dried at 100°C for 2 minutes. After the obtained coating film was cooled to room temperature, a high pressure mercury lamp was used to irradiate the substrate at 30 mW / cm 2 The liquid crystal orientation solidified layer C was obtained by irradiating ultraviolet rays with an intensity of 1000 nm for 30 seconds. The thickness of the liquid crystal orientation solidified layer was 3.0 μm, and the in-plane phase difference Re(550) was 130 nm. In addition, the Re(450) / Re(550) of the liquid crystal orientation solidified layer was 0.851, showing inverse wavelength dispersion characteristics. The liquid crystal orientation solidified layer was used as a phase difference layer.
[0111]
[0112] 20 parts by weight of a side chain liquid crystal polymer represented by the following chemical formula (I) (the numbers 65 and 35 in the formula represent the molar % of the monomer unit, and for convenience, it is expressed as a block polymer: weight average molecular weight 5000), 80 parts by weight of a polymerizable liquid crystal showing a nematic liquid crystal phase (manufactured by BASF: trade name Paliocolor LC242), and 5 parts by weight of a photopolymerization initiator (manufactured by Ciba Specialty Chemicals: trade name Irgacure907) are dissolved in 200 parts by weight of cyclopentanone to prepare a liquid crystal coating liquid. Then, the coating liquid is applied to a substrate film (norbornene-based resin film: manufactured by Zeon Co., Ltd., Japan, trade name "ZEONEX") using a rod coater, and then heated and dried at 80°C for 4 minutes to align the liquid crystal. The liquid crystal layer is irradiated with ultraviolet rays to cure the liquid crystal layer, thereby forming a liquid crystal orientation solidified layer (positive C plate, thickness 3μm) on the substrate to become another phase difference layer. The Re(590) of this layer is 0 nm, and the Rth(590) is -100 nm, showing the refractive index characteristics of nz>nx=ny.
[0113]
[0114] The liquid crystal orientation solidified layer C is transferred to the polarizer surface of the polarizer obtained in the above via an adhesive layer (thickness 5μm), and then the positive C plate is transferred to the surface of the liquid crystal orientation solidified layer C. A polarizer with a phase difference layer having a structure of a protective layer / adhesive / polarizer / adhesive layer / phase difference layer / adhesive / positive C plate is obtained as described above. The thickness of the obtained polarizer with a phase difference layer is 49μm. The polarizer with a phase difference layer is punched into a rectangle of a specific size corresponding to a bendable image display device having a bending axis along the short side direction. Here, the punching is performed in a manner that the absorption axis of the polarizer is 30° relative to the bending axis. The obtained polarizer with a phase difference layer is provided for the same evaluation as Example 1-1. The results are shown in Table 1.
[0115] [Example 2-2] to [Example 2-5] and [Comparative Example 2-1] to [Comparative Example 2-2]
[0116] The polarizing plate with a retardation layer was obtained in the same manner as in Example 2-1 except that the polarizer was punched out so that the angle between the absorption axis and the bending axis was the angle shown in Table 1. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0117] [Example 3-1]
[0118] Instead of the HC-TAC film, an acrylic resin film (thickness 20 μm) was used as a protective layer. Except for this, the same operation as in Example 1-1 was performed to obtain a polarizer with a phase difference layer. The elastic modulus of the protective film was 2881 MPa. In addition, the thickness of the obtained polarizer with a phase difference layer was 31 μm. The polarizer with a phase difference layer was punched into a rectangle of a specific size corresponding to a bendable image display device having a bending axis along the short side direction. Here, the punching was performed in such a way that the absorption axis of the polarizer was 30° relative to the bending axis. The obtained polarizer with a phase difference layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0119] [Example 3-2] to [Example 3-5] and [Comparative Example 3-1] to [Comparative Example 3-2]
[0120] The polarizing plate with a retardation layer was obtained in the same manner as in Example 3-1 except that the polarizer was punched out so that the angle between the absorption axis and the bending axis was the angle shown in Table 1. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0121] [Example 4-1]
[0122] Instead of the HC-TAC film, an acrylic resin film (thickness 40 μm) was used as a protective layer. Except for this, the same operation as in Example 1-1 was performed to obtain a polarizer with a phase difference layer. The elastic modulus of the protective film was 3066 MPa. In addition, the thickness of the obtained polarizer with a phase difference layer was 51 μm. The polarizer with a phase difference layer was punched into a rectangle of a specific size corresponding to a bendable image display device having a bending axis along the short side direction. Here, the punching was performed in such a way that the absorption axis of the polarizer was 30° relative to the bending axis. The obtained polarizer with a phase difference layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0123] [Example 4-2] to [Example 4-5] and [Comparative Example 4-1] to [Comparative Example 4-2]
[0124] The polarizing plate with a retardation layer was obtained in the same manner as in Example 4-1 except that the polarizer was punched out so that the angle between the absorption axis and the bending axis was the angle shown in Table 1. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0125] [Comparative Example 5-1]
[0126] A retardation layer (a single retardation layer that exhibits inverse wavelength dispersion dependence and functions as a λ / 4 plate) was produced as follows.
[0127] The polymerization was carried out using a batch polymerization apparatus consisting of two vertical stirring reactors equipped with stirring blades and reflux condensers. 30.31 parts by mass (0.047 moles) of bis[9-(2-phenoxycarbonylethyl)fluoren-9-yl]methane (BPFM) synthesized by the method described in Japanese Patent Application Laid-Open No. 2015-25111, 39.94 parts by mass (0.273 moles) of isosorbide (ISB, manufactured by Roquette Freres), 30.20 parts by mass (0.099 moles) of spiroglycol (SPG, manufactured by Mitsubishi Gas Chemical Co., Ltd.), 69.67 parts by mass (0.325 moles) of diphenyl carbonate (DPC, manufactured by Mitsubishi Chemical Co., Ltd.), and 7.88×10 -4 Mass parts (4.47×10 -6mol) of calcium acetate monohydrate as a catalyst. After the reactor was replaced with nitrogen under reduced pressure, it was heated by a heat medium and stirring was started at the time when the internal temperature reached 100°C. After 40 minutes from the start of heating, the internal temperature reached 220°C and was controlled to maintain this temperature. At the same time, the pressure was reduced and it took 90 minutes to reduce the pressure to 13.3 kPa after reaching 220°C. The phenol vapor produced as a by-product with the polymerization reaction was guided to a reflux condenser at 110°C, and a certain amount of monomer components contained in the phenol vapor was returned to the reactor. The uncondensed phenol vapor was guided to a condenser at 45°C for recovery. Nitrogen was introduced into the first reactor, and after the pressure was temporarily restored to atmospheric pressure, the oligomerized reaction liquid in the first reactor was moved to the second reactor. Next, heating and pressure reduction in the second reactor were started, and the internal temperature was changed to 240°C and the pressure was changed to 20 kPa within 40 minutes. Thereafter, polymerization was carried out while further reducing the pressure until the specified stirring power was reached. At the time point when the specified power is reached, nitrogen is introduced into the reactor for re-pressurization, the generated polyester carbonate is extruded into water, and the strands are cut to obtain pellets. The ratio of the structural units derived from each monomer of the resin is BPFM / ISB / SPG / DPC=21.5 / 39.4 / 30.0 / 9.1% by mass. The obtained pellets are vacuum dried at 100°C for more than 6 hours, and then a film-making device equipped with a single screw extruder (screw diameter of 25 mm manufactured by ISUZU Chemical Machinery Co., Ltd., barrel setting temperature of 250°C), a T-die (width of 300 mm, setting temperature of 220°C), a chilled roll (setting temperature of 120-130°C) and a winder is used to prepare a long unstretched film with a length of 3m, a width of 200mm, and a thickness of 100μm. The stretching temperature is set to Tg (139°C), and the long unstretched film is stretched to obtain a retardation film with a thickness of 37μm. The obtained retardation film showed a refractive index characteristic of nx>ny=nz, Re(550) was 145 nm, and Re(450) / Re(550) was 0.85.
[0128] Using the phase difference film obtained above as the phase difference layer, the phase difference film is attached to the polarizer via the adhesive layer (thickness 5 μm) instead of the adhesive layer, and the positive C plate used in Example 2-1 is transferred to the surface of the phase difference layer. In addition, the same operation as Example 1-1 is performed to obtain a polarizer with a phase difference layer having a protective layer / adhesive / polarizer / adhesive layer / phase difference layer (phase difference film) / adhesive / positive C plate. The thickness of the obtained polarizer with a phase difference layer is 89 μm. The polarizer with a phase difference layer is punched into a rectangle of a specific size corresponding to a bendable image display device having a bending axis along the short side direction. Here, the absorption axis of the polarizer is punched out in a manner that is 0° relative to the bending axis. The obtained polarizer with a phase difference layer is provided for the same evaluation as Example 1-1. The results are shown in Table 1.
[0129] [Comparative Example 5-2] to [Comparative Example 5-7]
[0130] The polarizing plate with a retardation layer was obtained in the same manner as in Comparative Example 5-1 except that the polarizer was punched out so that the angle between the absorption axis and the bending axis was the angle shown in Table 1. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0131] [Comparative Example 6-1]
[0132] A polarizing plate with a phase difference layer was obtained by the same operation as in Example 1-1 except that an HC-COP film was used as a protective layer instead of the HC-TAC film. The elastic modulus of the protective film was 1988 MPa. In addition, the thickness of the polarizing plate with a phase difference layer obtained was 84 μm. The polarizing plate with a phase difference layer was punched into a rectangle of a specific size corresponding to a bendable image display device having a bending axis along the short side direction. Here, the punching was performed in such a way that the absorption axis of the polarizer was 30° relative to the bending axis. The obtained polarizing plate with a phase difference layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0133] [Comparative Example 6-2] to [Comparative Example 6-7]
[0134] The polarizing plate with a retardation layer was obtained in the same manner as in Comparative Example 6-1 except that the polarizer was punched out so that the angle between the absorption axis and the bending axis was the angle shown in Table 1. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0135] [Comparative Example 7-1]
[0136] A polarizing plate was produced in the following manner.
[0137] A polyvinyl alcohol resin film having an average degree of polymerization of 2400, a saponification degree of 99.9 mol % and a thickness of 30 μm was prepared. The polyvinyl alcohol film was immersed in a swelling bath (water bath) at 20° C. for 30 seconds between rollers with different peripheral speed ratios to swell it, and at the same time, it was stretched to 2.4 times in the conveying direction (swelling process), and then immersed in a dyeing bath at 30° C. (an aqueous solution having an iodine concentration of 0.03 wt % and a potassium iodide concentration of 0.3 wt %) to dye it in a manner such that the monomer transmittance after the final stretching becomes a desired value, and at the same time, it was stretched to 3.7 times in the conveying direction based on the original polyvinyl alcohol film (polyvinyl alcohol film that was not stretched at all in the conveying direction) (dyeing process). The immersion time at this time was about 60 seconds. Next, the dyed polyvinyl alcohol film was immersed in a cross-linking bath at 40°C (aqueous solution with a boric acid concentration of 3.0% by weight and a potassium iodide concentration of 3.0% by weight), and at the same time, it was stretched to 4.2 times in the conveying direction based on the original polyvinyl alcohol film (cross-linking process). Furthermore, the obtained polyvinyl alcohol film was immersed in a stretching bath at 64°C (aqueous solution with a boric acid concentration of 4.0% by weight and a potassium iodide concentration of 5.0% by weight) for 50 seconds, stretched to 6.0 times in the conveying direction based on the original polyvinyl alcohol film (stretching process), and then immersed in a cleaning bath at 20°C (aqueous solution with a potassium iodide concentration of 3.0% by weight) for 5 seconds (cleaning process). The washed polyvinyl alcohol film was dried at 30°C for 2 minutes to prepare a polarizer (thickness 12μm). On one side of the obtained polarizer, the HC-TAC film was bonded in the same manner as in Example 1-1, and on the other side, a TAC film with a thickness of 25μm was bonded. A polarizing plate having a structure of viewing side protective layer (HC-TAC film) / polarizer / inner side protective layer (TAC film) was prepared as described above. The elastic modulus of the viewing side protective layer was 3872 MPa, similar to Example 1-1.
[0138] In addition to using the polarizer obtained above, the same operation as Comparative Example 5-1 is performed to obtain a polarizer with a phase difference layer having a structure of a protective layer / adhesive / polarizer / adhesive / protective layer / adhesive layer / phase difference layer (phase difference film) / adhesive / positive C plate. The thickness of the obtained polarizer with a phase difference layer is 116 μm. The polarizer with a phase difference layer is punched into a rectangle of a specific size corresponding to a bendable image display device having a bending axis along the short side direction. Here, the punching is performed in a manner that the absorption axis of the polarizer becomes 0° relative to the bending axis. The obtained polarizer with a phase difference layer is provided for the same evaluation as Example 1-1. The results are shown in Table 1.
[0139] [Comparative Example 7-2] to [Comparative Example 7-7]
[0140] The polarizing plate with a retardation layer was obtained in the same manner as in Comparative Example 7-1 except that the polarizer was punched out so that the angle between the absorption axis and the bending axis was the angle shown in Table 1. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0141] [Comparative Example 8-1]
[0142] A polarizing plate having the structure of brightness enhancement film / polarizer was prepared by laminating a single-sided brightness enhancement film (an amorphous isophthalic acid copolymer polyethylene terephthalate (IPA copolymer PET) film (thickness: 30 μm) having a water absorption of 0.75% and a Tg of 75°C) to the polarizer prepared in Comparative Example 7-1. The following sequence was performed in the same manner as in Example 1-1 to obtain a polarizing plate with a phase difference layer having the structure of protective layer (brightness enhancement film) / adhesive / polarizer / adhesive / W layer / adhesive / Q layer. The elastic modulus of the protective layer was 5005 MPa. In addition, the thickness of the obtained polarizing plate with a phase difference layer was 48 μm. The polarizing plate with a phase difference layer was punched out into rectangles of a specific size corresponding to a bendable image display device having a bending axis along the short side direction. Here, the punching was performed in such a manner that the absorption axis of the polarizer was 0° relative to the bending axis. The obtained polarizing plate with a phase difference layer was subjected to the same evaluation as in Example 1-1. Table 1 shows the results.
[0143] [Comparative Example 8-2] to [Comparative Example 8-7]
[0144] The polarizing plate with a retardation layer was obtained in the same manner as in Comparative Example 8-1 except that the polarizer was punched out so that the angle between the absorption axis and the bending axis was the angle shown in Table 1. The obtained polarizing plate with a retardation layer was subjected to the same evaluation as in Example 1-1. The results are shown in Table 1.
[0145] [Table 1]
[0146]
[0147] [evaluate]
[0148] As is clear from Table 1, according to the Examples of the present invention, it is possible to obtain a polarizing plate with a retardation layer that is excellent in both bending properties and visibility when viewed through polarized sunglasses.
[0149] Industrial Applicability
[0150] The polarizing plate with a retardation layer of the present invention can be suitably used in an image display device that is bendable and can be viewed through polarized sunglasses.
[0151] Explanation of symbols
[0152] 10 Polarizer
[0153] 11 Polarizer
[0154] 12. Protective layer
[0155] 20 Phase difference layer
[0156] 21 H floor
[0157] 22 Q Layer
[0158] 100 Polarizing film with phase difference layer
[0159] 102 Polarizing plate with phase difference layer.
Claims
1. A polarizing plate with a phase difference layer, which is a polarizing plate with a phase difference layer for a bendable image display device, comprising: A polarizing plate comprising a polarizer and a protective layer located on at least one side of the polarizer; and a phase difference layer, which is provided on the side of the polarizing plate opposite to the viewing side and has a circular polarization function or an elliptically polarization function, The total thickness of the polarizing plate with a retardation layer is 80 μm or less. The angle between the bending axis of the image display device and the absorption axis of the polarizer is 35° to 55°. The elastic modulus of the protective layer is less than 5000 MPa. The phase difference layer is an orientation solidified layer of liquid crystal compounds. The absorption axis of the polarizer is along one direction throughout the polarizer. 2 . The polarizing plate with a retardation layer according to claim 1 , wherein the total thickness is 60 μm or less.
3. The polarizing plate with a phase difference layer according to claim 1 or 2, wherein: The polarizer has a thickness of 10 μm or less.
4. The polarizing plate with a phase difference layer according to claim 1 or 2, wherein: The polarizing plate includes a protective layer only on the side of the polarizer opposite to the phase difference layer.
5. The polarizing plate with a phase difference layer according to claim 4, wherein: The elastic modulus of the protective layer is 4000 MPa or less.
6. The polarizing plate with a phase difference layer according to claim 5, wherein: The thickness of the protective layer is less than 45 μm.
7. The polarizing plate with a phase difference layer according to claim 1 or 2, wherein: The angle formed by the bending axis and the absorption axis of the polarizer is 40° to 50°.
8. The polarizing plate with a phase difference layer according to claim 1 or 2, wherein: The phase difference layer is a single layer, Re(550) of the phase difference layer is 100nm~190nm, Re(450) / Re(550) of the phase difference layer is greater than 0.8 and less than 1, and the angle between the slow axis of the phase difference layer and the absorption axis of the polarizer is 40°~50°.
9. The polarizing plate with a phase difference layer according to claim 8, wherein: The polarizing plate with a retardation layer further includes another retardation layer on the outer side of the retardation layer, and the refractive index characteristic of the other retardation layer shows a relationship of nz>nx=ny.
10. The polarizing plate with a phase difference layer according to claim 1 or 2, wherein: The phase difference layer has a stacked structure of an alignment solidified layer of a first liquid crystal compound and an alignment solidified layer of a second liquid crystal compound. The Re (550) of the alignment solidified layer of the first liquid crystal compound is 200 nm to 300 nm, and the angle between the slow axis and the absorption axis of the polarizer is 10° to 20°. The Re (550) of the alignment solidified layer of the second liquid crystal compound is 100 nm to 190 nm, and the angle formed between the slow axis and the absorption axis of the polarizer is 70° to 80°. 11 . An image display device comprising the polarizing plate with a retardation layer according to claim 1 .
Citation Information
Patent Citations
Liq. crystalline (LC) material
DE19504224A1
Novel polymerizable liquid crystalline compounds
DE4408171A1
Liquid crystalline reticulated polysiloxanes
EP0066137A1
Picture display cell, method of forming an orientation layer on a substrate of the picture display cell and monomeric compounds for use in the orientation layer
EP0261712A1
Liquid crystal polyorganosiloxanes containing (meth)acryloxy groups
EP0358208A2